(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The current article attempts to denote the relationship between the regulatory purpose of politics and law, which form coherent power as a dialectical unity of political power interested in the legal legitimation of its status and legal power, appealing to the power represented by the state, on the one hand, and their denial of each other as the embodiment of the paradigms of efficiency (politics) and legitimation (law), on the other hand. To meet that aim, general scientific (dialectical, comparative, historical-genetic, structural-functional), and also specific scientific (specific-sociological, formal-logical, historical-legal, comparative jurisprudence) methods are taken into consideration. Given the results of the study, the efficiency paradigm is determined by the factor of result, and the legitimation paradigm is determined by the factor of process. The interaction of these paradigms gives rise to an antinomic contradiction, which is an attributive characteristic of the political and legal regulation of social processes.